Levels of phonological awareness, working memory, and lexical knowledge in elementary school children - Bandini, Heloisa Helena Motta; Santos, Flávia Heloísa [UNESP]; Souza, Deisy das Graças de (FapUNIFESP (SciELO), 2013)
Relationships between oral language, phonological awareness, and working memory have been empirically demonstrated, however, phonological awareness encompasses different abilities, assessed at different levels. The present study investigated the possible associations between specific phonological awareness abilities and phonological working memory in first-grade students. In the initial phase (n = 254), the study evaluated the abilities of phonological awareness and phonological working memory and found a high positive correlation between these abilities, thus confirming the findings of previous studies. The second phase (n = 12) evaluated the vocabulary of individuals who, in the initial phase, showed low or high working memory and phonological awareness scores. Students with low working memory and low phonological awareness capacities had low scores in expressive language abilities, suggesting that phonological working memory may have direct effects on lexical knowledge. These results contribute to the understanding of the relationships investigated in this study and have important implications for planning teaching strategies.

Las relaciones entre lenguaje oral, conciencia fonológica y memoria operacional han sido mostradas empíricamente, pero la conciencia fonológica engloba habilidades diferentes, mensuradas en diferentes niveles. El objetivo de este trabajo, conducido en dos estudios, fue investigar las posibles asociaciones entre las sub-clases de habilidades de conciencia fonológica, memoria fonológica de niños del primero año escolar. En el primero estudio (n = 254), fueron evaluadas las habilidades de conciencia fonológica y memoria fonológica, que mostraron fuerte correlación positiva. En el segundo estudio (n = 12), fueron realizados test de vocabulario en niños con bajos y altos escores en memoria operativa y conciencia fonológica. Los niños con puntuaciones bajas en memoria operativa fonológica y conciencia fonológica presentaran habilidades del lenguaje expresivo reducidas, indicando que la memoria operativa fonológica parece interferir directamente en el vocabulario. Los resultados contribuyen hacia la comprensión de las relaciones investigadas y afectan el plan de enseñanza.

Relações entre linguagem oral, consciência fonológica e memória operacional têm sido demonstradas empiricamente, mas consciência fonológica engloba habilidades diferentes. Este artigo teve como objetivo investigar possíveis associações entre habilidades específicas de consciência fonológica e memória operacional fonológica em alunos do primeiro ano escolar. Na fase inicial (n = 254), o estudo avaliou habilidades de consciência fonológica e memória operacional fonológica e encontrou elevada correlação positiva entre ambas as habilidades, confirmando e estendendo resultados de estudos prévios. A segunda fase (n = 12) avaliou o vocabulário de indivíduos que obtiveram baixos ou altos escores em memória operacional e consciência fonológica na primeira fase. Os alunos com escores reduzidos de memória operacional e consciência fonológica obtiveram baixos escores em habilidades de linguagem expressiva, indicando que a memória operacional fonológica pode ter efeitos diretos sobre o conhecimento lexical. Esses resultados contribuem para a compreensão das relações investigadas e planejamento de estratégias de ensino.
Niveles de conciencia fonológica, memoria operativa y conocimiento lexical en niños escolares
Níveis de consciência fonológica, memória operacional e conhecimento lexical em escolares
Keywords: Working memory; Language; Reading; Phonological awareness; Memoria operacional; Lenguaje; Lectura; Conciencia fonológica; Memória operacional; Linguagem; Leitura; Consciência fonológica